2009
DOI: 10.6009/jjrt.65.285
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Radiation Protection for Workers in Positron Emission Tomography Facilities in Japan-1st Report: Occupational Role Assignment, Radiation Exposure to Medical Workers

Abstract: We have investigated the role assignment and radiation exposure of medical workers (including receptionists) in PET (positron emission tomography) facilities in Japan using a questionnaire. The survey period was from October 1st to November 15th 2006. The response rate for the questionnaire was 60.0% (72/120 facilities). Nurses were engaged in the intravenous administration of radioactive FDG in 66.9% of PET facilities. In 89.5% of PET facilities, radiological technologists mainly performed the PET examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies reported that the average radia-tion dose was approximately 24 µ Sv/day or approximately 0.1 mSv/month in nursing staff 6,10) ; however, these reports did not describe the physical and mental conditions of the patients. In the present study, the average ± SD for radiation dose per case was slightly higher (6.07 ± 5.71 µ Sv/case) than those in the previous reports.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies reported that the average radia-tion dose was approximately 24 µ Sv/day or approximately 0.1 mSv/month in nursing staff 6,10) ; however, these reports did not describe the physical and mental conditions of the patients. In the present study, the average ± SD for radiation dose per case was slightly higher (6.07 ± 5.71 µ Sv/case) than those in the previous reports.…”
Section: Discussionmentioning
confidence: 96%
“…The burdens of nursing care are increasing for patients who have low activities of daily living (ADL) indices or impaired cognitive function because 18 F-FDG PET/CT is increasingly used to examine them. Furthermore, the radiation exposure doses of nursing staff during PET examinations are increasing in Japan 6) . The principles of radiation protection, i.e., exposure time, distance, and shielding, are always adhered-to for any procedure involving radioactive administration.…”
mentioning
confidence: 99%